Policy seminar: Leveraging Kenya’s new Bottom-Up Economic Plan for food system transformation - Mbuthia, Juneweenex; Omune, Lensa (International Food Policy Research Institute, 2022)
Kenya’s new government has developed an ambitious Bottom-Up Economic Plan to tackle complex domestic and global challenges. “The Bottom-Up approach is about making sure that markets work, and more importantly, work for the poor,” Cabinet Secretary Prof. Njuguna Ndung’u explained during a recent policy seminar hosted by the Kenya Institute for Public Policy Research and Analysis (KIPPRA) and IFPRI Kenya as part of the CGIAR Research Initiative on National Policies and Strategies (NPS) seminar series.